Asymmetric information acquisition in credit auctions - Tröge, Michael (online, 1999)
Abstract:
urn:nbn:de:0168-ssoar-194785
Keywords: (stw)Bank; (stw)Kreditgeschäft; (stw)Wettbewerb; (stw)Informationsverhalten; (stw)Kreditwürdigkeit; (stw)Informationsökonomik; (stw)Wohlfahrtsanalyse; (stw)Theorie; (thesoz)Kreditwesen; (thesoz)Beschaffung; (thesoz)Kreditvergabe; (thesoz)ökonomisches Modell; (thesoz)Marktform; (thesoz)Bankgewerbe; (thesoz)Wettbewerb; (thesoz)Information; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Bank; Kreditgeschäft; Wettbewerb; Informationsverhalten; Kreditwürdigkeit; Informationsökonomie; Wohlfahrtseffekt; Theorie